2022
DOI: 10.3389/fmolb.2021.801401
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals of Euphorbia hirta L. and Their Inhibitory Potential Against SARS-CoV-2 Main Protease

Abstract: Euphorbia hirta L. is a medicinal plant widely used in the Philippines and across tropical Asia against various diseases, including respiratory disorders. In this study, the phytochemical components of E. hirta were investigated in silico for their potential to inhibit the severe acute respiratory syndrome-coronavirus-2 main protease (SARS-CoV-2 Mpro), a coronavirus disease 2019 (COVID-19) drug target that plays a critical role in the infection process of SARS-CoV-2. Phytochemical mining in tandem with virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Flavonoids and phenols have been noticed in E. serpens only, while terpenes and tannins found in E. prostata and E. hirta respectively. The results also were compatible with previously reported by [20], about the phtytocomponents of E. hirta, however, the researchers [6], identified flavonoids as mostly contain phytochemical constituents in Euphorbia serpens, alkaloids and saponins were identified by [21], in Euphorbia hypercifolia. The most effect biochemical compounds alkaloids, flavonoids, terpenes and saponins are found in nonpolar solvent hexane (Table .7).…”
Section: Photochemical Screeningsupporting
confidence: 92%
See 1 more Smart Citation
“…Flavonoids and phenols have been noticed in E. serpens only, while terpenes and tannins found in E. prostata and E. hirta respectively. The results also were compatible with previously reported by [20], about the phtytocomponents of E. hirta, however, the researchers [6], identified flavonoids as mostly contain phytochemical constituents in Euphorbia serpens, alkaloids and saponins were identified by [21], in Euphorbia hypercifolia. The most effect biochemical compounds alkaloids, flavonoids, terpenes and saponins are found in nonpolar solvent hexane (Table .7).…”
Section: Photochemical Screeningsupporting
confidence: 92%
“…Nevertheless, different types of terpenes have been isolated from E. milii var. milii [19][20][21]. The chromatogram of the GC-MS analysis of six taxa of Euphorbia illustrated the peaks of the chemical compounds, molecular weight, molecular formula, area as well as their retention time were reported in Figure 1-6…”
Section: Gc/ms Analysismentioning
confidence: 98%
“…Potential ligand-binding sites of the solution structure of H-NS Ctd (PDB ID: 2L93) were predicted using POCASA 1.1 42 and molecular docking analysis by AutoDock Vina 1.1.2 43 showed that the best conformation of the H-NS Ctd -c-di-GMP complex (Fig. 3d) has the lowest docking score of − 7.0 kcal mol − 1 , which is below the threshold value of − 6 kcal mol − 1 for considering effective protein-ligand binding 44 . This conformation suggests that c-di-GMP makes close contact with Y99, D101, K107, R114, T115, P116, A117, V118 and K121 of H-NS Ctd (Fig.…”
Section: H-ns Directly and Speci Cally Binds To C-di-gmpmentioning
confidence: 99%